1690. Oral Fosfomycin for the Treatment of Bacterial Prostatitis. (31st December 2020) - Kamath, Meghan; Johns, Scott T; Ma, Ariel; Mehta, Sanjay
Abstract: Background: Bacterial prostatitis (BP) is notoriously difficult to treat. Few antibiotics penetrate the prostate well, and antibiotic resistance can further restrict options. A small body of recent literature suggests fosfomycin, a bactericidal antibiotic that can treat multidrug resistant (MDR) organisms and has little cross-resistance, may both effectively penetrate the prostate and treat BP. This study sought to add to the limited literature on the efficacy and safety of fosfomycin for BP. Methods: Patients treated for BP with fosfomycin between November 2009 and May 2019 at the San Diego VAMC were retrospectively examined. Patients were excluded if they died within 6 months of completion of fosfomycin or if fosfomycin was used for less than half of the treatment course. If fosfomycin was used to treat a urinary tract infection (UTI), an infectious disease physician determined if the UTI may have been undiagnosed BP. Outcomes were clinical and microbiological cure at 6 months and adverse events to fosfomycin reported during the trial period. Results: The study included 29 patient cases. All but one had chronic BP. Most initially presented outpatient (66%). Almost all had prior occurrences of BP treated with antibiotics (90%). The most common pathogen was E. coli (73%), and 87% of all pathogens were MDR. The most common fosfomycin dosing regimen was 3g PO q48h (66%), with 3g PO q24h as the next most common (21%). Less than half of patient cases received fosfomycin courses > 28 days (38%), while the remaining received courses < 14 days (62%). At 6 months, 48% achieved clinical cure and 44% achieved microbiological cure. When comparing those who received courses > 28 days vs. courses < 14 days, clinical cure was achieved in 55% vs. 44% and microbiological cure in 56% vs. 39%, respectively. Adverse events were reported in 6 unique patients (27%), mostly diarrhea with one instance of nausea. Conclusion: Fosfomycin may be a safe and effective alternative for the treatment of chronic BP. Treatment courses longer than 4 weeks may be more effective than courses shorter than 2 weeks with a similar rate of adverse events. This study also highlights inpatients as a relevant BP population and a need for provider education on identifying BP and prescribing optimal durations of therapy. Disclosures: All Authors : No reported disclosures